Nanorepairers Rescue Inflammation‐Induced Mitochondrial Dysfunction in Mesenchymal Stem Cells (Adv. Sci. 4/2022). Issue 4 (3rd February 2022) - Zhai, Qiming; Chen, Xin; Fei, Dongdong; Guo, Xiaoyan; He, Xiaoning; Zhao, Wanmin; Shi, Songtao; Gooding, John Justin; Jin, Fang; Jin, Yan; Li, Bei
Abstract : Mesenchymal Stem Cells Chronic inflammation leads to mitochondrial Ca 2+ overload and the inhibition of mitophagy due to activation of Wnt/ β ‐catenin pathway in mesenchymal stem cells (MSCs). As a result, dysfunctional mitochondria impair the differentiation of MSCs. In article number 2103839, Xin Chen, Fang Jin, Yan Jin, Bei Li, and co‐workers engineer a novel "nano‐repairs", capturing Ca 2+ around mitochondria and eliminating the dysfunctional mitochondria. "Nano‐repairs" physiologically restore the function of mitochondria and MSCs, which provide therapy for inflammatory bone diseases.